Bacteriuria asintomática en adultos mayores con nefropatía crónica - Granda Matute, Yamira Solange (Machala : Universidad Técnica de Machala, 2019)
Asymptomatic bacteriuria is considered to be the presence of bacteria that exceed 100,000 CFU / ml in urine, without these presenting symptoms. Objective to update the medical knowledge about asymptomatic bacteriuria in older adults with a history of chronic renal failure. Materials and methods descriptive study based on the review of indexed scientific articles from the last 5 years’ stories such as PubMed, Cochrane, Ministry of Health Guide, Journal American. Results Echerichia Coli continues to be the causative agent of asymptomatic bacteriuria in more than 80% of cases, the treatment is given as long as this merits makes the adjustment of the corresponding dose; as well as due hygienic dietary standards, improving lifestyles and thereby reducing the colonization of bacteria Conclusion in patients with chronic kidney disease are more likely to suffer from this disease due to dilation of the collecting tubule which facilitates bacterial colonization.
Se considera bacteriuria asintomática a la presencia de bacterias que sobrepasan 100.000 UFC/ml en orina, sin que estas presenten sintomatología. Objetivo Actualizar los conocimientos médicos sobre bacteriuria asintomática en adultos mayores con antecedentes de insuficiencia renal crónica. Materiales y métodos estudio descriptivo basado en la revisión de artículos científicos indexados de los últimos 5 años tales como PubMed, Cochrane, Guía Ministerio de Salud, Journal American. Resultados La Echerichia Coli sigue siendo el agente causal de bacteriuria asintomática en más 80% de los casos, el tratamiento se da siempre y cuando este lo amerite realizando el ajuste de la dosis correspondiente; así como las debidas normas higiénico dietéticas, mejorando estilos de vida y disminuyendo de tal manera la colonización de bacterias Conclusión en los pacientes con nefropatía crónica tienen mayor probabilidad de padecer esta enfermedad debido a que desarrollan dilatación del túbulo colector lo que facilita la colonización bacteriana.
Keywords: BACTERIURIA; ASINTOMATICA; NEFROPATIA; PATOGENOS